Low-warpage ultrahigh-rigidity chopped fiber reinforced PP (polypropylene) special material as well as preparation and application thereof

Through the improvement of the formulation and the use of gas-phase silica and silane coupling agent KH-590, combined with large-particle inorganic fillers, the warping problem of chopped fiber-reinforced polypropylene materials is solved, and the mechanical properties and shrinkage consistency is improved. It is suitable for in automotive stand and other fields.

CN119320530APending Publication Date: 2025-01-17CGN TOXXON (XIAMEN) NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411540845.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Short-cut fiber reinforced polypropylene materials are prone to warping during injection molding, mainly due to the large differences in shrinkage rates in different directions, and the existing technology has not effectively solved this problem.

Method used

By improving the formulation, including the use of gas-phase silica and silane coupling agent KH-590, combined with large-particle inorganic fillers such as titanium dioxide and talc, the crystal structure of PP resin and the distribution of chopped fibers, improve the phase of the material Capacitive and mechanical properties, silane coupling agent is added to side feed to enhance the synergistic effect of the inorganic filler and PP resin.

Benefits of technology

It significantly reduces the warpage of the material, improves the mechanical properties and weather resistance of PP sheets, ensures the unity of horizontal and vertical shrinkage, and meets the performance needs of the automotive industry for plastic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320530A_ABST
    Figure CN119320530A_ABST
Patent Text Reader

Abstract

The invention discloses a low-warpage ultrahigh-rigidity chopped fiber reinforced PP (polypropylene) special material, a preparation method thereof and application thereof in the field of manufacturing PP plates or automobile brackets. The low-warpage ultrahigh-rigidity chopped fiber reinforced PP special material is prepared from the following raw materials in parts by weight: 40 to 75 parts of PP resin, 10 to 25 parts of chopped glass fiber, 5 to 10 parts of composite inorganic filler, 2 to 5 parts of flexibilizer and 1 to 2 parts of silane coupling agent KH-590, the composite inorganic filler comprises a large-particle-size inorganic filler and an auxiliary small-particle-size inorganic filler; the large-particle-size inorganic filler comprises at least one of titanium dioxide, barium sulfate, mica powder and talcum powder; the particle size of the large-particle-size inorganic filler is 10-200 [mu] m; the auxiliary small-particle-size inorganic filler is fumed silica, and the particle size of the fumed silica is 7-50 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chopped fiber reinforced polypropylene (PP) materials, and in particular to a low-warpage ultra-high rigidity chopped fiber reinforced PP special material and a preparation method and application thereof. Background Art

[0002] At present, the PP reinforcement materials used in the market are generally directly filled with glass fiber reinforcement materials to improve the strength of the material. Long fibers have good performance but are difficult to process. Compared with short fibers, they are more likely to cause floating fibers, agglomeration and other undesirable phenomena, which seriously affect the appearance and performance of PP materials; short fibers are easy to process and not easy to float fibers, but due to their small size, they are easy to be oriented along the flow direction during the injection molding process, resulting in a large difference in shrinkage along the flow direction and the shrinkage perpendicular to the flow direction, thus causing warping.

[0003] The patent specification with publication number CN117534906A discloses a high-rigidity, low-shrinkage talc-filled flame-retardant polypropylene material and a preparation method. The high-rigidity, low-shrinkage talc-filled flame-retardant polypropylene material is made of polypropylene, low-halogen flame retardant, ultrafine talc, coupling agent, compatibilizer, nucleating agent, lubricant, and antioxidant mixed in a twin-screw extruder for extrusion and granulation, wherein the ultrafine talc is first modified with a coupling agent, and the coupling agent is at least one of a titanate coupling agent, an aluminate coupling agent, and a silane coupling agent. The ultrafine talc has a mesh size of 5000 mesh and a SiO2 content of ≥58%. Although the patent technology focuses on the shrinkage index of the material, it does not further study the shrinkage difference of the material in different directions, which is attributed to the fact that the material is not actually a PP material reinforced with short fibers. It is unknown whether the patent technology solution can be directly transferred and applied to PP materials reinforced with short fibers to solve the problem of shrinkage difference in different directions of the material.

[0004] The patent specification with publication number CN117327346A discloses a high light-shielding, high whiteness, high strength and low shrinkage PP material and its preparation method. The PP material comprises the following raw materials: 55-65 parts of PP, 5-35 parts of rutile titanium dioxide, 15-45 parts of talc, 5-15 parts of chopped glass fiber, 0.3-0.6 parts of antioxidant, 0.4-0.8 parts of lubricant, and 0.3-0.6 parts of light stabilizer; wherein the PP is made by mixing homopolymer PP and copolymer PP in a mass ratio of 1.75-2.25:1; the mesh number of rutile titanium dioxide is 1500-2000 mesh; the mesh number of talc is 1500-2000 mesh. In addition, the talc is pretreated by the following method: dispersing the talc in a silane coupling agent, stirring at 60-65°C for 20-30 minutes, washing with water, filtering, and then dispersing in anhydrous ethanol, adding active silicon powder, stirring at 85-90°C for 2-3 hours, filtering, and obtaining pretreated talc. Similarly, although the patent technology focuses on the shrinkage index of the material, it does not further study the differences in shrinkage in different directions of the material.

[0005] The main reason for material warping is that the shrinkage rate of the material in different directions is quite different. Therefore, in order to overcome the problem of easy warping of chopped fiber reinforced PP materials, reducing the difference in shrinkage rate of the material in different directions is the key. Summary of the invention

[0006] In view of the above technical problems and the deficiencies in the art, the present invention provides a low-warpage ultra-high rigidity short-cut fiber reinforced PP special material and its preparation method and application. The present invention greatly improves the performance of PP through the improvement of the formula, and at the same time, the more uniform and fine crystal structure reduces the internal stress of PP, so that PP has a higher anti-warpage ability. The present invention can solve the warpage deformation problem caused by the different shrinkage rates of short-cut fiber filled PP materials in all directions, and improve the mechanical properties of PP sheets to meet the performance requirements of automotive plastic parts in the automotive industry.

[0007] [1] A low-warpage ultra-high rigidity chopped fiber reinforced PP special material, the raw material composition includes, by weight: 40-75 parts of PP resin, 10-25 parts of chopped glass fiber, 5-10 parts of composite inorganic filler, 2-5 parts of toughening agent, and 1-2 parts (preferably 1.5-2 parts) of silane coupling agent KH-590;

[0008] The composite inorganic filler comprises a large-particle-size inorganic filler and an auxiliary small-particle-size inorganic filler;

[0009] The large-particle inorganic filler includes at least one of titanium dioxide, barium sulfate, mica powder, and talcum powder; the particle size of the large-particle inorganic filler is 10-200 μm;

[0010] The auxiliary small-particle inorganic filler is fumed silica (gas silica), and the particle size of the fumed silica is 7-50 nm.

[0011] The present invention aims at the characteristics of chopped fibers and performs volume modification on PP resin to further optimize its performance: the size distribution of fumed silica is 7-50nm, and it has a high specific surface area. It can act as a nucleating agent to further reduce and regularize the crystal structure of PP, making the PP resin easier to cool and increasing the difficulty of displacement of the chopped fibers. At the same time, the fumed silica is evenly dispersed in the PP resin, and combined with fillers such as talcum powder with a larger particle size, it further hinders the uniform orientation of the chopped fibers. In addition, the silane coupling agent KH-590 is added to the side feed during the injection molding process to further produce a synergistic effect, greatly improving the compatibility of inorganic fillers including chopped fibers with PP resin, and significantly improving its mechanical properties and weather resistance. This is of great significance to the application of PP sheets.

[0012] The silane coupling agent KH590 used in the present invention has methoxy and mercapto groups, and can react with maleic anhydride grafted toughening agents to increase the compatibility between PP resin, glass fiber, and inorganic fillers such as gas silica. Studies have found that other silane coupling agents such as KH550 amino groups are alkaline and KH560 epoxy groups have almost no effect, and are not suitable for the system of the present invention.

[0013] The low-warpage ultra-high rigidity chopped fiber reinforced PP special material, the PP resin can be at least one of homopolymer PP, random copolymer PP and block copolymer PP.

[0014] If the molecular weight distribution of PP resin is too large, it will contain unwanted small molecules and super large molecules. These small molecules have poor weather resistance and super large molecules affect fluidity, which are both undesirable.

[0015] In some embodiments, the molecular weight distribution of the homopolymer PP is ≤3, the melt index at 230°C / 2.16kg is 10±5g / 10min, and the density is 0.8-1.0g / cm 3 After cooling for 72 hours, the shrinkage rate is 1.2-1.5%.

[0016] In some embodiments, the molecular weight distribution of the random copolymer PP and the block copolymer PP is ≤3, the 230°C / 2.16kg melt index is independently 15±5g / 10min, and the density is independently 0.8-1.0g / cm 3 , and after cooling for 72 hours, the shrinkage rates were independently 0.8%-1.5%.

[0017] In the present invention, the shrinkage test method is to inject the material into 100mm×4mm×4mm strips (5 pieces each), and let it stand at room temperature for 72 hours to achieve full shrinkage, thereby measuring the length, width and height of the strips after shrinkage to calculate the shrinkage in different directions.

[0018] The low-warpage ultra-high rigidity chopped fiber reinforced PP special material, the chopped glass fiber is 4-5 mm (for example, 4.5 mm, etc.) long and 12-14 μm (for example, 13 μm, etc.) in diameter.

[0019] In some embodiments, the low warpage ultra-high rigidity chopped fiber reinforced PP special material, measured in parts by weight, comprises 0.5-2 parts of fumed silica, for example, 0.5 parts, 1 part, 1.5 parts, 2 parts, etc.

[0020] In some embodiments, the low-warpage ultra-high rigidity chopped fiber reinforced PP special material, the large-particle inorganic filler includes titanium dioxide and talcum powder. Further, the weight ratio of the titanium dioxide to the talcum powder can be 4:3.

[0021] In some embodiments, the low-warpage ultra-high rigidity chopped fiber reinforced PP special material, in terms of weight, comprises 4.5-8 parts of the large-particle inorganic filler, such as 6 parts, 7 parts, etc.

[0022] The low-warpage ultra-high rigidity chopped fiber reinforced PP special material, the toughening agent may include at least one of ethylene propylene copolymer grafted maleic anhydride, ethylene octene copolymer grafted maleic anhydride, and ethylene propylene diene monomer rubber grafted maleic anhydride.

[0023] The density of the low-warpage ultra-high rigidity chopped fiber reinforced PP special material and the silane coupling agent KH-590 can be 1.02-1.06 g / cm 3 , the refractive index can be 1.440±0.005.

[0024] The low-warpage ultra-high rigidity short-cut fiber reinforced PP special material, the raw material composition may also include an antioxidant. The weight portion of the antioxidant may be 0.5-3 parts. The antioxidant may include a primary antioxidant and a secondary antioxidant. The primary antioxidant may include at least one of antioxidant 1010, antioxidant 1076, and antioxidant 1098. The secondary antioxidant may include at least one of antioxidant 626 and antioxidant 168. The addition weight ratio of the primary antioxidant to the secondary antioxidant may be 1:1 to 2:1.

[0025] The low-warpage ultra-high rigidity short-cut fiber reinforced PP special material may further include a lubricant in the raw material composition. The weight portion of the lubricant may be 0.5-1.5 parts. The lubricant may include at least one of polyethylene wax, ethylene bis fatty acid amide, silicone masterbatch, and pentaerythritol stearate.

[0026] [2] The method for preparing the low-warpage ultra-high-rigidity chopped fiber reinforced PP special material according to [1] comprises:

[0027] The PP resin, composite inorganic filler, toughening agent, and optionally added antioxidant and lubricant are mixed and added to the main feeding port of the twin-screw extruder, and the chopped fibers and silane coupling agent KH-590 are added to the side feeding port of the twin-screw extruder. After being melted and extruded by the twin-screw extruder, the low-warpage ultra-high rigidity chopped fiber reinforced PP special material is obtained.

[0028] The preparation method of the present invention feeds the silane coupling agent KH-590 and the chopped fibers together into a twin-screw extruder by side feeding. Compared with feeding the silane coupling agent KH-590 as the main feed into the twin-screw extruder, on the one hand, the problem of uneven mixing of the main feed caused by the small proportion of the silane coupling agent KH-590 can be avoided, and on the other hand, the problem that the silane coupling agent KH-590 is consumed by the reaction of components such as PP resin and composite inorganic filler before the main raw material components are plasticized and cannot further take effect on the chopped fibers can be avoided. The silane coupling agent KH-590 of the present invention is fed together with the chopped fibers by side feeding into the twin-screw extruder. At this time, the main raw material components have been plasticized, and the silane coupling agent KH-590 can better react with the chopped fibers to take effect, thereby improving the mechanical properties, weather resistance and warpage resistance of the composite material.

[0029] The temperature of each zone of the barrel of the twin-screw extruder can be set to 170-230° C., and the screw speed can be 380-420 rpm, such as 400 ppm.

[0030] [3] Application of the low warpage ultra-high rigidity chopped fiber reinforced PP special material according to [1] in the production of PP sheets or in the field of automobile brackets.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention solves the technical problems of high warpage, non-uniform lateral and longitudinal shrinkage and poor mechanical properties of current short-fiber reinforced PP plastics by improving the formula, further improves weather resistance by increasing crystallinity, and develops a special short-fiber reinforced PP material with low warpage and ultra-high rigidity suitable for technical fields such as automobile brackets. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1These are the electron microscopic photograph of the horizontal cross-section (injection molding direction) (A) and the electron microscopic photograph of the vertical cross-section (B) of the product of Example 7, as well as the electron microscopic photograph of the horizontal cross-section (injection molding direction) (C) and the electron microscopic photograph of the vertical cross-section (D) of the product of Example 3. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0035] Some of the raw materials used in the following examples are introduced as follows:

[0036] The molecular weight distribution of homopolymer PP is ≤3, the melt index at 230℃ / 2.16kg is 10±5g / 10min, and the density is 0.8-1.0g / cm 3 , after cooling for 72 hours, the shrinkage rate is 1.2-1.5%;

[0037] The molecular weight distribution of random copolymer PP is ≤3, the melt index at 230℃ / 2.16kg is 15±5g / 10min, and the density is 0.8-1.0g / cm 3 , after cooling for 72 hours, the shrinkage rate is 0.8%-1.5%;

[0038] The chopped glass fiber is 4.5 mm long and 13 μm in diameter;

[0039] The particle size of titanium dioxide and talc is distributed between 10-200 μm;

[0040] The particle size of fumed silica is 7-50nm;

[0041] The density of silane coupling agent KH-590 is 1.02-1.06g / cm 3 , the refractive index is 1.440±0.005.

[0042] Example 1

[0043] (1) Weigh the following components by weight: homopolymer PP: 52 parts, random copolymer PP: 8 parts, chopped glass fiber: 12 parts, ethylene propylene copolymer grafted maleic anhydride: 4 parts, titanium dioxide: 4 parts, talc: 3 parts, fumed silica: 0.5 parts, polyethylene wax: 0.5 parts, silicone masterbatch: 0.5 parts, antioxidant 1098: 0.25 parts, antioxidant 626: 0.25 parts.

[0044] (2) The raw materials other than the chopped glass fibers are mixed uniformly in a high-speed mixer and added from the main feed port of a twin-screw extruder. The chopped glass fibers are fed from the side feed port and then melt-extruded through a twin-screw extruder at a temperature of 170-230° C. and a screw speed of 400 rpm. The products are then cooled, dried, and cut into pellets to obtain the product.

[0045] Example 2

[0046] The only difference from Example 1 is that the amount of fumed silica is changed to 1 part by weight, and the rest is the same.

[0047] Example 3

[0048] The only difference from Example 1 is that the amount of fumed silica is changed to 1.5 parts by weight, and the rest is the same.

[0049] Example 4

[0050] The only difference from Example 1 is that the amount of fumed silica is changed to 2 parts by weight, and the rest is the same.

[0051] Example 5

[0052] (1) Weighing each component by weight: The only difference from Example 3 (1) is that 1.5 parts by weight of silane coupling agent KH-590 is additionally weighed, and the rest are the same.

[0053] (2) The raw materials other than the chopped glass fiber and the silane coupling agent KH-590 are mixed uniformly in a high-speed mixer and then added from the main feeding port of the twin-screw extruder. The chopped glass fiber is fed from the side feeding port, and the silane coupling agent KH-590 is dripped from the side feeding port. The mixture is then melt-extruded through the twin-screw extruder at a temperature of 170-230° C. and a screw speed of 400 rpm. The mixture is then cooled, dried, and cut into pellets to obtain the product.

[0054] Example 6

[0055] The only difference from Example 5 is that the silane coupling agent KH-590 is changed to 2 parts by weight, and the rest is the same.

[0056] Example 7

[0057] The only difference from Example 1 is that the amount of fumed silica is changed to 0 parts by weight, and the rest is the same.

[0058] Table 1 shows the performance test results of each product, where the bending strength test method is based on GB9341, the tensile strength test method is based on GB1040, and the impact strength is the cantilever beam notched impact strength test method based on GB1843. The shrinkage test method is to inject each material into 100mm×4mm×4mm splines (5pcs each), and let it stand at room temperature for 72h to achieve full shrinkage, so as to measure the length, width and height of the splines after shrinkage to calculate the shrinkage in different directions.

[0059] Table 1

[0060]

[0061] From the test results of Examples 1-7, it can be seen that fumed silica acts as an inorganic small-particle filler and exerts a good synergistic effect. Inorganic fillers of different particle sizes make the PP system structure more compact and short-range ordered. From Example 7 and Examples 1 to 4, it can be seen that as the proportion of fumed silica increases, smaller-sized inorganic fillers are filled into PP, and in cooperation with large-particle fillers, they hinder the orientation of the glass fiber after injection molding, making the glass fiber tend to be isotropic, thereby making the lateral shrinkage rate and the longitudinal shrinkage rate tend to be consistent. Figure 1 The corresponding phenomenon can also be observed in (A) and (B): Compared with the obvious anisotropy of the glass fibers in (A) and (B), the glass fibers in (C) and (D) are more disordered and do not show uniform transverse or longitudinal directions. At the same time, fumed silica also acts as a nucleating agent, which improves the regularity of PP, enhances rigidity, and reduces the overall shrinkage. As the addition amount reaches 2 parts, the impact strength of Example 4 decreases significantly. It can be seen from this trend that if excessive fumed silica is added, the material will tend to be rigid and the impact resistance will be greatly reduced. At the same time, fumed silica is very light, and excessive addition has the disadvantage of being difficult to unload. Taking all factors into consideration, Example 3 has better comprehensive performance. In addition, the reason why the impact strength of the material in Example 1 is improved compared with that in Example 7 may be that the trace amount of fumed silica is more evenly dispersed, effectively dispersing stress inside the material, and preventing the expansion of cracks to a certain extent. The material density of Examples 1 to 4 is greater than that of Example 7 because the introduction of fumed silica increases the crystallinity of the material, and at the same time, the density of fumed silica itself is large, which makes the material density of Examples 1 to 4 slightly increased compared with Example 7.

[0062] By adding a silane coupling agent on the basis of Example 3, the compatibility of the inorganic filler, glass fiber and PP resin is further adjusted, and the mechanical properties of Examples 5 and 6 are improved, but there is little difference between Examples 5 and 6. By comparing Example 7 with Examples 5 and 6, it can be found that after adding fumed silica and silane coupling agents, the mechanical properties of the material are improved, and while the shrinkage rate is reduced, the horizontal and vertical shrinkage rates also tend to be consistent. Due to the process difficulties (if the amount of silane coupling agent is increased, it is difficult to extrude too much liquid), adding 1-2 parts of silane coupling agent KH-590 to the side feed is the optimal solution. And such a technical solution of the present invention also achieves excellent product performance under low silane coupling agent KH-590 addition.

[0063] Through the above technical scheme, the present invention solves the technical problems of high warpage, non-uniform lateral and longitudinal shrinkage and poor mechanical properties of current PP plastics by improving the formula, and develops low-warpage ultra-high rigidity short-cut fiber reinforced PP special materials suitable for technical fields such as automobile brackets.

[0064] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A low-warpage ultra-high rigidity chopped fiber reinforced PP special material, characterized in that: The raw material composition includes, by weight: 40-75 parts of PP resin, 10-25 parts of chopped glass fiber, 5-10 parts of composite inorganic filler, 2-5 parts of toughening agent, 1-2 parts of silane coupling agent KH-590 (preferably 1.5-2 parts); The composite inorganic filler comprises a large-particle-size inorganic filler and an auxiliary small-particle-size inorganic filler; The large-particle inorganic filler includes at least one of titanium dioxide, barium sulfate, mica powder, and talcum powder; the particle size of the large-particle inorganic filler is 10-200 μm; The auxiliary small-particle inorganic filler is fumed silica, and the particle size of the fumed silica is 7-50 nm.

2. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The PP resin is at least one of homopolymer PP, random copolymer PP and block copolymer PP; The molecular weight distribution of the homopolymer PP is ≤3, the melt index at 230°C / 2.16kg is 10±5g / 10min, and the density is 0.8-1.0g / cm 3 , after cooling for 72 hours, the shrinkage rate is 1.2-1.5%; The molecular weight distribution of the random copolymer PP and the block copolymer PP is ≤3, the 230°C / 2.16kg melt index is independently 15±5g / 10min, and the density is independently 0.8-1.0g / cm 3 , and after cooling for 72 hours, the shrinkage rates were independently 0.8%-1.5%.

3. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The chopped glass fibers are 4-5 mm long and 12-14 μm in diameter; In parts by weight, the raw material composition includes 4.5-8 parts of the large-particle inorganic filler; In parts by weight, the raw material composition includes 0.5-2 parts of fumed silicon dioxide.

4. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The toughening agent includes at least one of ethylene propylene copolymer grafted with maleic anhydride, ethylene octene copolymer grafted with maleic anhydride, and ethylene propylene diene monomer rubber grafted with maleic anhydride.

5. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The density of the silane coupling agent KH-590 is 1.02-1.06 g / cm 3 , the refractive index is 1.440±0.

005.

6. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The raw material composition also includes an antioxidant; The weight proportion of the antioxidant is 0.5-3 parts; The antioxidant includes a primary antioxidant and a secondary antioxidant; The primary antioxidant includes at least one of antioxidant 1010, antioxidant 1076, and antioxidant 1098; The auxiliary antioxidant includes at least one of antioxidant 626 and antioxidant 168; The weight ratio of the primary antioxidant to the secondary antioxidant is 1:1 to 2:

1.

7. The low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to claim 1, characterized in that: The raw material composition also includes a lubricant; The weight percentage of the lubricant is 0.5-1.5 parts; The lubricant includes at least one of polyethylene wax, ethylene bis fatty acid amide, silicone masterbatch, and pentaerythritol stearate.

8. The method for preparing the low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to any one of claims 1 to 7, characterized in that: include: The PP resin, composite inorganic filler, toughening agent, and optionally added antioxidant and lubricant are mixed and added to the main feeding port of the twin-screw extruder, and the chopped fibers and silane coupling agent KH-590 are added to the side feeding port of the twin-screw extruder. After being melted and extruded by the twin-screw extruder, the low-warpage ultra-high rigidity chopped fiber reinforced PP special material is obtained.

9. The preparation method according to claim 8, characterized in that: The temperature of each zone of the barrel of the twin-screw extruder is set to 170-230° C., and the screw speed is 380-420 rpm.

10. Use of the low-warpage ultra-high rigidity chopped fiber reinforced PP special material according to any one of claims 1 to 7 in the production of PP sheets or in the field of automobile brackets.

Citation Information

Patent Citations

  • High-shading, high-whiteness, high-strength and low-shrinkage PP material and preparation method thereof

    CN117327346A

  • High-rigidity low-shrinkage talcum powder filled flame-retardant polypropylene material and preparation method thereof

    CN117534906A

Cited By

  • High-toughness polypropylene plastic particle modified material

    CN119931208A